LINC02323 facilitates development of lung squamous cell carcinoma by miRNA sponge and RBP dysregulation and links to poor prognosis. Issue 4 (14th December 2022) - Wu, Kuan‐Li; Tsai, Ying‐Ming; Huang, Yung‐Chi; Wu, Yu‐Yuan; Chang, Chao‐Yuan; Liu, Yu‐Wei; Hsu, Ya‐Ling; Hung, Jen‐Yu
Abstract: Background: The poor outcome of patients with lung squamous cell carcinoma (LUSC) highlights the importance of the identification of novel effective prognostic markers and therapeutic targets. Long noncoding RNAs (lncRNAs) have generally been considered to serve important roles in tumorigenesis and the development of various types of cancer, including LUSC. Methods: Here, we aimed to investigate the role of LINC02323 in LUSC and its potential mechanisms by performing comprehensive bioinformatic analyses. Results: LINC02323 was elevated and positively associated with unfavorable prognosis of LUSC patients. LINC02323 exerted oncogenic function by competitively binding to miR‐1343‐3p and miR‐6783‐3p, thereby upregulating L1CAM expression. Indeed, we also determined that LINC02323 could interact with the RNA‐binding protein DDX3X, which regulates various stages of RNA expression and processing. Conclusion: Taken together, we identified that LINC02323 and its indirect target L1CAM can act as novel biomarkers for determining the prognosis of patients with LUSC and thus deserves further study. Abstract : LINC02323 sponges miR‐1343‐3p and miR‐6783‐3p and upregulates L1CAM for promoting LUSC progression. An RNA‐binding protein DDX3X is proposed to modulate LINC02323 expression.